Analisis Sumber Dan Penggunaan Modal Kerja Terhadap Modal Kerja - Muktiadji, Nusa; Lia, Lia (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
The sources and uses of fund is a report presented by company to determine changes in financial position for each period. Company manager has resposibility of where the fund isobtained and how it is used. Each company is involved in various investment activities and expenditures. When carrying out those activities, the company produces fund. The fund is defined as cash and cash equivalents and it can also be interpreted as working capital. Working capital is defined as total current assets (gross working capital) or the difference or balance between current assets and debts (net working capital). The purpose of this study is to analyze the sources and uses of fund and to analyze the stage of corporate liquidity. The analysis conducted to determine whether the activity of sources and uses of working capital and liquidity increase or decrease in each period. The result shows that PT Indosat, Tbk. and PT XL Axiata, Tbk. use aggresive strategy to manage their working capital. It is evidenced by the existence of negative working capital each year and it has fluctuating liquidity. However when the two companies are compared, PT Indosat, Tbk. is better than PT XL Axiata, Tbk., especially in the stage of liquidity. The result of the evaluation shows that the working capital reduction of PT Indosat, Tbk. and PT XL Axiata, Tbk. produces negative number. It can be looked at the calculation of sources and uses as well as the liquidity stage of PT Indosat, Tbk. and PTXL Axiata, Tbk. Based on the result of this evaluation, the author suggest PT Indosat, Tbk. and PT XL Axiata, Tbk. reduce their curret debts, so that working capital generated can be increased. Specifically for PT XL Axiata, Tbk., itâs suggested to make existing cash of the company is not small any more.